The photoredox-catalyzed hydrosulfamoylation of styrenes and its application in the novel synthesis of naratriptan. Issue 72 (19th August 2021) - Zhang, Mingjun; Chen, Miaomiao; Ding, Xin; Kang, Jin; Gao, Yongyue; He, Xingxing; Wang, Ziwen; Lu, Aidang; Wang, Qingmin
Abstract : The use of sulfamoyl chlorides as precursors of sulfamoyl radicals has enabled the efficient hydrosulfamoylation of diverse styrenes and has provided a convenient approach for the synthesis of naratriptan. Abstract : The hydrosulfamoylation of diverse aryl olefins provides facile access to alkylsulfonamides. Here we report a novel protocol utilizing radical-mediated addition and a thiol-assisted strategy to achieve the hydrosulfamoylation of diverse styrenes in modest to excellent yields under mild and economic reaction conditions. The methodology was found to provide an efficient and convenient approach for the synthesis of the anti-migraine drug naratriptan and it also can be used for the late-stage functionalization of natural products or medicines.